2021
DOI: 10.1148/radiol.2021204021
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Algorithm Improves Radiologist Performance in Skeletal Age Assessment: A Prospective Multicenter Randomized Controlled Trial

Abstract: T he accurate determination of a child's developmental status is required for proper treatment of various growth disorders (1) and scoliosis (2). Other parameters, such as height, weight, secondary sexual characteristics, chronologic age, and dental age, correlate with developmental status, but skeletal age has been considered the most reliable method (3-5). The standard of care for this assessment calls for radiologists to identify the reference standard in an atlas of hand radiographs that most closely resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 30 publications
1
70
0
1
Order By: Relevance
“…10 In related work, several groups reported that AI algorithms can identify various demographic patient factors. One study 11 found that an AI model could predict sex and distinguish between adult and paediatric patients from chest x-rays, while other studies 12 reported reasonable accuracy at predicting the chronological age of patients from various imaging studies. In ophthalmology, retinal images have been used to predict sex, age, and cardiac markers (eg, hypertension and smoking status).…”
Section: Introductionmentioning
confidence: 99%
“…10 In related work, several groups reported that AI algorithms can identify various demographic patient factors. One study 11 found that an AI model could predict sex and distinguish between adult and paediatric patients from chest x-rays, while other studies 12 reported reasonable accuracy at predicting the chronological age of patients from various imaging studies. In ophthalmology, retinal images have been used to predict sex, age, and cardiac markers (eg, hypertension and smoking status).…”
Section: Introductionmentioning
confidence: 99%
“…BoneXpert’s accuracy is MAD 4.1 months, compared to 4.9 months for a prominent deep learning method 19 .…”
Section: Discussionmentioning
confidence: 94%
“…Many deep learning-based bone age methods have been presented starting with the RSNA Challenge in 2017 6 . The most thoroughly validated method is the one from Stanford 19 , which achieved a MAD of 4.9 months on the RSNA test set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent prospective RCT in radiology studied the effect of a deep learning model for bone age prediction on reader accuracy and interpretation time. 38 The future of artificial intelligence in medicine is more likely to demonstrate physician and machine working together rather than independently; thus, evaluating how deep learning can augment retina specialists in their provision of care is the next logical step.…”
Section: Future Directionsmentioning
confidence: 99%